The Interaction between Market and Non-Market Based Energy and Environmental Regulations to Reduce Carbon Emissions: A Case Study of California and British Columbia - Koester, Stefan. (Tufts University. Tisch Library., 2019)
National and sub-national governments have pursued dual-paths to reduce GHG emissions to mitigate climate change. States have carbon pricing schemes and non-market-based policies such as renewable energy mandates, vehicle, building, and appliance standards, tax credits and subsidies for low-carbon energy. However, what is the possible interactive effect between market and non-market-based policies? This thesis attempts to answer this question for California and British Columbia. California has had a cap-and-trade program since 2012 along with other climate and energy related policies. British Columbia has had a carbon tax since mid-2009, with a number of energy and efficiency standards. Using the synthetic control method (SCM), I attempt to isolate and measure the effect of carbon pricing programs on additional, per-capita GHG emissions reductions. Results are inconclusive as to the interactive relationship between market and non-market-based policies, however the SCM holds potential for future analyses in the energy and environmental domains.; Thesis (M.A.)--Tufts University, 2019.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisors: Ann Rappaport, and Kelly Sims-Gallagher.; Keywords: Environmental economics, and Energy.